Perceptions of honey bee management information sources among backyard and sideliner beekeepers in the United States. (December 2022) - Engebretson, Jesse M.; Nelson, Kristen C.; Steinhauer, Nathalie; Rennich, Karen; Spivak, Marla; vanEngelsdorp, Dennis
Abstract : In recent decades, there has been an increase in people learning about and practicing beekeeping in rural, peri-urban and urban across the United States. Yet, much recent honey bee research focuses on the biotic (e.g., mites and viruses) and abiotic (e.g., pesticides and management practices) factors contributing to colony loss. However, beekeepers themselves play an essential role in stewarding healthy and productive colonies. This study focuses on backyard and sideliner beekeepers who responded to an annual online survey distributed in the U.S. (n = 2155) in 2018. This paper investigates beekeepers' concerns, and their use and perception of honey bee management information sources. We found survey respondents to be a relatively homogeneous group. Our findings suggest beekeepers' primary concerns relate to biotic and abiotic drivers of colony loss and the socio-political aspects of honey bee management. Also, beekeepers use, perceive as useful, and trust different types of information in consistent ways. For example, networks developed in beekeeping club interactions with beekeeping scientists are often used, viewed as useful, and highly trusted. Thus, information distribution through such channels may increase the likelihood of impactful and resonant communication exchanges among researchers, educators, and beekeepers, perhaps leading to the more widespread use of Best Management Practices that address risk factors to mitigate future colony loss. Highlights: Beekeepers are concerned about Varroa, general disease, and pesticide exposure. Personal experience, mentors, and clubs are perceived as useful information sources. Scientists, experience, and mentors are perceived as trustworthy information sources. Clubs and mentor programs can be resonant sites for information sharing and practice.